1984
DOI: 10.1126/science.223.4642.1265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Ds Controlling Element Mutations at the Adh1 Locus of Maize

Abstract: An active maize Adhl-F gene, a Ds-induced mutant of this gene, and two independent Ac-induced revertant alleles have been isolated. The Ds mutant differs from the progenitor allele in having a 405-base pair insertion flanked by a direct repeat of 8 bp. The repeat is a duplication of the 8 bp existing at the point of insertion in the 5' untranslated region of the gene. The insertion sequence is AT-rich (A, adenine; T, thymine) and has 11-bp inverted repeat sequences at its termini. In the revertants the inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(111 citation statements)
references
References 21 publications
3
106
0
Order By: Relevance
“…Transactivation of inactive, Ds-like, elements has helped in elucidating transposition factors and could be useful for controlled transposon tagging [32]. The deleted forms of the transposable elements Tam3 and Ac might be used to set up artificial two-element systems.…”
Section: Discussionmentioning
confidence: 99%
“…Transactivation of inactive, Ds-like, elements has helped in elucidating transposition factors and could be useful for controlled transposon tagging [32]. The deleted forms of the transposable elements Tam3 and Ac might be used to set up artificial two-element systems.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) In the case of a cauliflower mosaic virus strain which contains a mutation resulting in a partial processing of the cauliflower mosaic virus 35S RNA (in the wild-type strain the 35S RNA does not appear to be spliced), it is one of the most A+U-rich RNA regions that is spliced out (18). (iii) Transposable element sequences located in the coding regions of different maize genes are frequently spliced out, partially restoring a wild-type phenotype (21,44,47,51). In most instances, the A+U content of these sequences is high.…”
mentioning
confidence: 99%
“…The integration of excised Ds::HPT elements into the rice genome was demonstrated by analyzing Ds::HPT sequences in the hygromycin-resistant caUi which were obtained by culturing transfected protoplasts. In one-third of the resistant calli, the integration of excised Ds::HPTwas found and 8 bp direct repeats, which are produced as a consequence of duplication of a target site upon integration of Ac/Ds (D6ring et aL, 1984;Pohlman et aL, 1984;Sutton et aL, 1984), flanked the integrated Ds::HPT. The analysis of the empty target site sequence clearly showed that 8 bp direct repeats were produced upon integration of Ds::HPT.…”
Section: Discussionmentioning
confidence: 99%
“…Eight base pair direct repeats flank the Ds in five out of six calli. Because Ac/Ds elements induce duplication of a target site of 8 bp upon integration (D6ring et al, 1984;Pohlman et al, 1984;Sutton et aL, 1984), the 8 bp direct repeats observed here were likely to have been generated upon integration of Ds::HPT. This was verified by analyzing the integration site in untransformed rice DNA ( Figure 5).…”
Section: Transformation Of Rice Protoplasts By Ds::h Ptmentioning
confidence: 95%